2022
DOI: 10.1097/pg9.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Postviral Gastroparesis Associated With SARS-CoV-2 Infection in a Pediatric Patient

Abstract: Postviral gastroparesis has been described in children, but it has not yet been attributed to SARS-CoV-2 infection. Our case report describes a teenager with abdominal pain, early satiety, and vomiting who likely had an asymptomatic SARS-CoV-2 infection 2 months before presentation. Through investigation of epidemiologic links, antibody testing, and clinical course, it is hypothesized that her significant reduction in gastric emptying was due to postviral gastroparesis secondary to SARS-CoV-2. She was treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Preclinical studies demonstrated the ability of aqueous extract of C. cassia Presl bark (150 and 300 mg/kg) to enhance gastric emptying and to promote GI transit that are both delayed in some Long COVID‐19 patients, suffering from a complex pathological picture‐defined autoimmune GI dysmotility (Montalvo et al, 2022; Sebai et al, 2019). These effects may be relevant also in patients with SARS‐CoV‐2‐induced gastric motility alterations (Patel et al, 2022; Rusch et al, 2022). Furthermore, in vivo experiments have shown that water extracts derived from the bark of C. cassia (150 mg/kg) significantly reduce the extent of gastric mucosa injuries caused by indomethacin, NSAIDs, ethanol, and ethanol/hydrochloric acid.…”
Section: The Phytocomplexmentioning
confidence: 99%
“…Preclinical studies demonstrated the ability of aqueous extract of C. cassia Presl bark (150 and 300 mg/kg) to enhance gastric emptying and to promote GI transit that are both delayed in some Long COVID‐19 patients, suffering from a complex pathological picture‐defined autoimmune GI dysmotility (Montalvo et al, 2022; Sebai et al, 2019). These effects may be relevant also in patients with SARS‐CoV‐2‐induced gastric motility alterations (Patel et al, 2022; Rusch et al, 2022). Furthermore, in vivo experiments have shown that water extracts derived from the bark of C. cassia (150 mg/kg) significantly reduce the extent of gastric mucosa injuries caused by indomethacin, NSAIDs, ethanol, and ethanol/hydrochloric acid.…”
Section: The Phytocomplexmentioning
confidence: 99%
“…After investigation of the epidemiologic links, antibody testing, and a clinical course, the patient was diagnosed with post-viral GP due to COVID-19. She was treated with supportive care and prokinetic agents and demonstrated symptom resolution and the near normalization of gastric emptying by the time of her 1-month follow-up [ 112 ].…”
Section: Exogenous Infections As Trigger Of Gastroparesismentioning
confidence: 99%